Steaming Effect on Natural Durability of Bamboo Oriented Strand Board against Termites and Powder Post Beetle - Fauzi Febrianto; Intan Purnamasari; Arinana Arinana; Adiyantara Gumilang; Nam H Kim (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The objective of this research was to evaluate the resistance of bamboo oriented strand board (BOSB) prepared from steamed and non-steamed strands of five (5) bamboo species against subterranean termite (Coptotermes curvignathus), dry wood termite (Cryptotermes cynocephalus), and powder post beetle. The five bamboo species were betung, andong, ampel, hitam, and tali. In steaming treatment, bamboo strands were steamed in autoclave at 126 °C and 1.4 kg cm-2 pressure for 1 h prior mixing with adhesive. Strands were bonded into BOSB by the use of commercial Phenol formaldehyde (PF) adhesive at 10% (w/w) of oven dried strands. The resistance of BOSB against termite was done based on SNI 01.7207-2006 procedures and requirement. The results indicated that the resistance of BOSB against termites was significantly affected by bamboo species and steam treatment. The resistance of BOSB prepared from steamed bamboo strands against C. curvignathus and C. cynocephalus was higher than that of non-steamed bamboo strands particularly that of ampel bamboo strands. The powder post beetle was identified as Anobium sp. Bamboo species and strands steaming did not significantly influence the resistance of BOSBs against Anobium sp.Key words: bamboo, dry wood termite, oriented strand board, powder post beetles, subterranean termite